Selection of students in the sports section of physiological mobility indicators - Nebesnaya V.V.; Gridina N.A.; Kashuba Y.V. (Fizičeskoe Vospitanie Studentov, 2012)
It is examined the relationship between the structural units coaching impacts and responses to them, the body of athletes. The study involved 60 athletes aged 16-18 years. A comparative analysis of physiological parameters of different types of functional mobility of the surveyed sports and physical activity assessment of the impact on the physical performance of athletes is shown. It is established that the appropriate training sessions and to determine the positive effect of physical activity, you need to take into account individual typological features of the central nervous system.